Age-and sex-specific seasonal variation of venous thromboembolism in patients with and without family history: a nationwide family study in Sweden - Zöller, Bengt; Li, Xinjun; Ohlsson, Henrik; Sundquist, Jan; Sundquist, Kristina (Thrombosis and Haemostasis, 2013)
Seasonal variation in venous thromboembolism (VTE) risk in individuals with familial predisposition to VTE has not been explored. This nationwide study aimed to determine whether there are age- and sex-specific seasonal differences in risk of hospitalisation of VTE among individuals with and without a family history of VTE. The Swedish Multi-Generation Register was linked to Hospital Discharge Register data for the period 1964–2010. Seasonal variation in first VTE events in 1987–2010 for individuals with and without a family history of VTE (siblings or parents) was determined by several independent methods. Stratified analyses were performed according to age, sex, and VTE subtype (pulmonary embolism [PE] or deep venous thrombosis [DVT]). Seasonal variation in VTE incidence, mostly with a peak during the winter, was observed in both sexes in individuals with and without family history with overall peak-to-low ratios (PLRs) of 1.15 and 1.21, respectively. The peak day was December 25 and February 1 for those with and without a family history of VTE, respectively. Seasonal variation was strongest among individuals aged >50 years. Among individuals aged 0–25 years with a family history, the peak for VTE was in July (PLR = 1.20). Significant seasonal variation was observed for PE and DVT with the exception of DVT among those with a family history (PLR = 1.01). In conclusion, our data support the presence of a modest seasonal variation of VTE among individuals with and without a family history of VTE. However, young age and family history may modify and attenuate the effect of season on VTE.
Keywords: Venous thrombosis; epidemiology; seasons; risk factors; familial thrombosis